Fracture behaviour of triaxial braided composites and its simulation using a multi-material shell modelling approach. (1st February 2018) - García-Carpintero, A.; van den Beuken, B.N.G.; Haldar, S.; Herráez, M.; González, C.; Lopes, C.S.
Highlights: Characterization of translaminar fracture behavior of triaxial braided composites. Detailed analysis of fracture mechanisms. Methodology for the simulation of fracture at structual level of braided composites. Abstract: The translaminar fracture response of triaxial braided composites was analysed by means of Compact Tension tests. Different values of critical strain energy release rate for fracture along the main material directions were estimated by applying two different data reduction methods to the experimental results. The fracture mechanisms were analysed to provide physical justification for such anisotropic behaviour. Possible laminate thickness effects were studied but judged to have negligible impact in the fracture toughness of these materials. A numerical methodology based on a Multi Material Shell approximation is proposed to simulate fracture of triaxial braided composites. The modelling approach is based on the discretization of the braiding architecture at the Gauss point level of standard shell elements including the corresponding yarn geometrical parameters. At constitutive level, Continuum Damage Models were used to simulate independently the brittle orthotropic yarns and the elasto-plastic isotropic resin matrix. This approach was validated by correlation between simulations of the Compact Tension tests and the corresponding experimental results. In spite of the modelling simplifications, the remarkable results achieved reveal an efficient virtual testing approach that can be used for the analysis fracture of triaxial braided materials at structural level.